Taxonomic status of the genus Spermophilus (Mammalia: Rodentia) in Turkey and Iran with description of a new species - Özkurt, Şakir Önder; Sözen, Mustafa; Yiğit, Nuri; Kandemir, Irfan; Çolak, Reyhan; Gharkheloo, Mohammed Moradi; Çolak, Ercüment (Zootaxa, 2007)
We report a new species of Spermophilus ( Rodentia: Sciuridae), here designated as S. torosensis sp. nov., distributed in the Taurus Mountains in southern Anatolia, Turkey. A total of 161 specimens of the genus Spermophilus from Turkey and Iran were analyzed for their morphological, morphometric, and karyological characteristics. Uni- and multi-variate statistical analyses of morphologic data for 95 adult specimens yielded 4 distinct groups. Taxonomic evaluations classified the specimens into 4 species Spermophilus citellus, S. xanthopymnus, S. fulvus and S. torosensis sp. nov. Morphometrics, coat coloration, a brush-shaped tail, and a NFa value of 72 are diagnostic characters that distinguish S. torosensis sp. nov. from the other species. In Turkey, S. torosensis sp. nov. was found in 6 locations. The karyotype of S. fulvus also is described for the first time as 2n= 36, NFa= 70 and NFa= 66; new karyotypic data is reported for S. xanthoprymnus from Iran and Turkey.